(untitled) (Philosophy and Progress, 2022)
It is difficult to identify nature with an exact meaning. Depending on circumstances and perspectives the term “nature” has various meanings ranging from spiritual participatory to mechanistic understanding. Having these complexities and ambiguous connotations the current research tries to investigate into some conceptual understanding of nature regarding traditional ideas and modern scientific views. There will also be an endeavor to see nature from a short historical survey. The paper aims to examine these conceptions in the light of environmental sustainability: which understanding of nature seems better to reform the dominating attitudes of humans toward the natural environment? Being critical of conventional and secular meanings of nature, the current paper proceeds to show how an understanding of a different kind can allow humans to behave with their surroundings. In so doing, the present study wants to shed more lights on natural environment, and to add more knowledge to the present discussions of ecological equilibrium. Philosophy and Progress, Vol#69-70; No#1-2; Jan-Dec 2021 P 173-188